Reforms in the Military Affairs of the Turkish Khanate and the Early Medieval Central Asian States - Rozimova Yorqinoy Yuldashevna (Research Parks Publishing LLC, 2021)
This article provides extensive information on the armies formed in the states that ruled in the Middle Ages, as well as the development of martial arts in the wars waged by them. It should be noted that today it is difficult to summarize all the information we have learned in one article, so in the process of preparing this article, after studying the work done in this area, published books, scientific pamphlets, this article is devoted to the development of armies of the Middle Ages. necessary military historical data related to the gradual development of art, combat strategy and tactics were included.